Microtus kirgisorum - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus kirgisorum (Ognev, 1950). [Mammals of USSR and Adjacent Countries], 7:219. TYPE LOCALITY: Kazakhstan, Tuyouk, Khirgiski Mtns. DISTRIBUTION: Recorded from S Kazakhstan, Kirghizia, Tadzhikistan, and SE Turkmenistan; may also occur in N Afghanistan. COMMENTS: Subgenus Microtus, arvalis species group sensu Zagorodnyuk (1990). Originally described as a subspecies of M. arvalis but later elevated to a separate species (Meier, 1983; Meier et al., 1981), as observed by Corbet (1984) and Pavlinov and Rossolimo (1987). Chromosomal data presented by Orlov et al. (1983) in context of phylogenetic study among members of the M. arvalis group. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 523, DOI: 10.5281/zenodo.7353098